Cultural identities of diáspora : myth and empowerment in Desirable daughters and The tree bride, by Bharati Mukherjee - Barbosa, Cleusa Salvina Ramos Maurício (2011)
By examining the constitution of identity/ies related to women s diaspora in contemporary times, the present thesis focuses on its representation in two novels written by the Indian born U.S. writer, Bharati Mukherjee Desirable Daughters (2002), and The Tree Bride (2004). I argue that these two novels offer excellent cultural manifestations for the examination of the representation of the identitary process resulting from transnational displacements. Centred on the field of Cultural Studies, the first part of this study presents readings of the women protagonists´ identitary quest portrayed in the novels informed by the major concepts of diasporic identities, hybrid identities and transnationalisms, as they have been theorized by Stuart Hall, Inderpal Grewal, and Homi K. Bhabha. The analyses contained in the second and the third parts of this thesis draw from studies in the area of Gender Studies, and present reflections on the main characters´ trajectories which are illuminated by the central notions of agency, performativity, and empowerment, theorized by Judith Butler and Luce Irigaray. Studies on mythology both from non-feminist and feminist perspectives also provide a backdrop for the readings proposed. The thesis is structured in three chapters: the first one discusses the constitution of diasporic identities, particularly the main character s; the second chapter concentrates on the gender-marked appropriation of mythical discourse by the author in the composition of her narratives by means of the literary strategy of feminist revisionist mythmaking, as pointed out by Alicia Ostriker; and the third section analyzes the protagonist s actions, viewing her process of empowerment as a transformative strategy in terms of subjective development which is strongly marked by gender issues. The main results of the analysis carried out is the perception that, by combining the shaping of diasporic identities, the rewriting of myth, and the deployment of empowerment strategies in the composition of the main characters in her novels, Bharati Mukherjee problematizes the diasporic woman subject s identity formation in relation to the India/U.S. movement, revisiting and reweaving Indian traditions from multifaceted and gender-marked perspectives. This, in turn, may act in terms of raising readers´ understanding and critical awareness of the women subjects´ diasporic process in the contemporary world.